Contrastive Study of Passive Voice of Intransitive Verbs in English and German a Based on the Construal Theory (Global Journal of Human-Social Science, 2018)
English and German have not only similarities but also differences in many ways From the perspective of cognitive linguistics either in English or German the passive voice of intransitive verbs is a special language phenomenon The Construal Theory of Langacker s cognitive grammar will be used to contrast and analyse the differences and cognitive reasons for the passive voice of intransitive verbs in English and German from different dimensions of construal The purpose of this analysis and the contrastive outcome is to help trilingual learners comprehensively and profoundly understand the two languages
Keywords: construal theory; intransitive verbs; passivevoice; contrastive